KERAGAMAN DAN HERITABILITAS SEMBILAN GENOTIP TOMAT (Lycopersicum esculentum Mill.) PADA BUDIDAYA ORGANIK - Putri Istianingrum; Damanhuri . (Jurnal Agroekoteknologi, 2016)
In breeding activities, the testing of new varieties for a particular environmentneeds germplasm with high variability and genetic information, including thevalue of heritability estimates. The research was aimed to know the variability and estimate heritability value on 9 genotypes of tomato on organic farming. The research was conducted at Torongrejo village, Junrejo subdistrict, Batu, East Java at the altitude of ± 700 m above sea level. The research used the Randomized Completely Block Design with three replications and 9 genotypes of F5 generation as treatment. Selection was done in organic breeding that specified in applying organic pesticide and fertilizer without any synthetic chemicals. Data of the observation was analyzed to find out the analysis of variance (anova), coefficient of genotypic and phenotypic variances and heritability. The results showed that the number of pieces of good character, the number of total fruit, fruit weight was good, ugly fruit weight, fruit weight and the total weight per piece had high values for the coefficient of genotypic and phenotypic variability. Result of the heritability calculation on characters number of good fruit, good fruit weight and weight per fruit had low values.Keywords: Tomatoes, Genotypic and phenotypic variability, Heritability,Organic farming